ANALISIS KELAYAKAN USAHA AGROWISATA KAMPOENG RABBIT’S DI KELURAHAN MENTANGOR KECAMATAN TENAYAN RAYA KOTA PEKANBARU PROVINSI RIAU - Khairizal; Refni Dwi Safitri; Azharuddin M Amin; Khairuddin (DINAMIKA PERTANIAN, 2022)
Agrotourism is a tourist activity that involves the use of agricultural land or related facilities that become an attraction for tourists. Agriculture in the broadest sense includes people's agriculture, plantations, livestock, fisheries, and forestry. This study aims to analyze: The financial viability of the agrotourism business kampoeng rabbit's. The research method is a survey method, on the agrotourism business kampoeng rabbit's in the Village of Mentangor District Tenayan Raya Kota Pekanbaru. The study was conducted for 6 months starting from August 2020 to January 2021. The respondents in this study were entrepreneurs and 8 workers. Furthermore, this study was analyzed descriptively quantitatively, business analysis, investment criteria (Net Present Value, Internal Rate Of Return, Net B /C and Payback Period). The types of data used are secondary data and primary data. The results of this study showed that the financial feasibility analysis of the ecotourism business kampoeng rabbit's worthy because it has met 4 investment criteria with an NPV value of 637,900,658 > 0, Net B / C 1.17 > 1, IRR 29% > 12% payback rate for 2 years 11 months 2 days < business life (10 years).